SEMIOTIC ANALYSIS ON TOY STORY 4 MOVIE: A THEORY OF ROLAND BARTHES - Sibagariang, Ruth (Prologue: Journal on Language and Literature, 2026)
This study aims to analyze the signs and meanings found in the animated film Toy Story 4 using Roland Barthes' semiotic theory. This study focuses on identifying the denotative, connotative, and mythological meanings found in selected characters and dialogues from the film. This study uses a qualitative research method, in which data is collected by carefully watching the film, selecting important scenes and dialogues, and analyzing them through Barthes' semiotic framework. This analysis explores how the signs in the film function not only as narrative elements but also as representations of deeper social and cultural meanings. The results show that several characters, such as Woody, Forky, Bo Peep, and Gabby Gabby, represent different symbolic meanings related to leadership, identity, independence, acceptance, and the desire for love and recognition. At the denotative level, the characters and dialogues convey literal meanings based on their roles in the story. At the connotative level, they express emotional and social meanings such as responsibility, self-esteem, and personal. Lastly, the mythological level reveals broader cultural values related to acceptance, empathy, courage in the face of change, and understanding one's role in society. Moral messages will also be drawn based on the myths found in the film.